2016
DOI: 10.1007/s10508-016-0848-6
|View full text |Cite
|
Sign up to set email alerts
|

Gay, Mostly Gay, or Bisexual Leaning Gay? An Exploratory Study Distinguishing Gay Sexual Orientations Among Young Men

Abstract: (2017) 'Gay, mostly gay, or bisexual leaning gay? An exploratory study distinguishing gay sexual orientations among young men.', Archives of sexual behavior., 46 (1). pp. 265-272. Further information on publisher's website:https://doi.org/10.1007/s10508-016-0848-6Publisher's copyright statement:The nal publication is available at Springer via https://doi.org/10.1007/s10508-016- Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…In one study, mostly heterosexual men showed more genital arousal and pupil dilation to female than male sexual stimuli, but still responded more strongly to both sexes than exclusively heterosexual men (Savin-Williams, . Correspondingly, mostly homosexual men appear more bisexual in their genital arousal, if not pupil dilation patterns, than homosexual men (Savin-Williams, Cash, McCormack, & Rieger, 2017;Semon, Hsu, Rosenthal, & Bailey, 2017). However, it has not been systematically investigated how the arousal patterns of mostly heterosexual and mostly homosexual men compare to those of men who report bisexual attractions with equal preferences.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In one study, mostly heterosexual men showed more genital arousal and pupil dilation to female than male sexual stimuli, but still responded more strongly to both sexes than exclusively heterosexual men (Savin-Williams, . Correspondingly, mostly homosexual men appear more bisexual in their genital arousal, if not pupil dilation patterns, than homosexual men (Savin-Williams, Cash, McCormack, & Rieger, 2017;Semon, Hsu, Rosenthal, & Bailey, 2017). However, it has not been systematically investigated how the arousal patterns of mostly heterosexual and mostly homosexual men compare to those of men who report bisexual attractions with equal preferences.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The increased range of gendered behaviors documented above has also problematized traditional understandings of sexuality, which has typically been understood as having three categories: heterosexuality, bisexuality, and homosexuality. However, the lack of flexibility within these categories has resulted in a growing body of research incorporating multiple sexual identities along a sexuality continuum (see Savin-Williams, Cash, McCormack & Rieger, 2017). This means, for example, that men can engage in sex with other men without being labeled as gay-as was not the case in previous generations, where men were immediately homosexualized for doing so (Anderson, 2008).…”
Section: Inclusive Masculinity and Bisexualitymentioning
confidence: 99%
“…This measure can even be a valid indicator for certain diseases, such as Parkinson's (Wang, McInnis, Brien, Pari, & Munoz, 2016). On the other hand, pupillometry is a rather coarse measure that often cannot provide specific predictions (failure in predicting sexual orientation: Savin- Williams, Cash, McCormack, & Rieger, 2016). In any case, it is important to keep in mind, that all these changes in pupil size are subtle and can be easily overruled by a ray of light falling onto the eye.…”
Section: Pupillometrymentioning
confidence: 99%